A Mediating Model of Emotional Balance and Procrastination on Academic Performance - Diotaiuti, Pierluigi; Valente, Giuseppe; Mancone, Stefania; Bellizzi, Fernando (Frontiers in Psychology, 2021)
Deficit in the management of time continues to be an important difficulty students are faced with. The present work aimed to test the hypothesis that self-regulation is the major predictor of academic performance and that this effect can be mediated both by the student’s emotional regulation and his propensity for procrastination. Participants were 450 university students who were administered MPP (Caprara, et al., 2006) and AIP (McCown & Johnson, 1989). The procedures involved the administration of instruments and the collection of average exam grades as a measure of academic performance. Two mediation analyses were conducted within a cross-sectional design. The effect of a specific component of self-regulation on academic performance, namely action orientation, was significant, while procrastination showed a limiting effect on the performative quality of the student. The model confirmed the mediation role of emotional balance on the effect that action orientation exerts on procrastination, and the mediation of procrastination in the relationship between action orientation and Academic Performance. Results of the study suggest focusing student support and prevention of procrastinating behavior on programs that enhance first of all student’s proactive attitude, planning skills, self-monitoring and effective/efficient time management, and secondly, emotional awareness and regulation of emotional response in situations of stress and performance anxiety.